Tyrocidines, cyclic decapeptides produced by soil bacilli, as potent inhibitors of fungal pathogens - Troskie, Anscha Mari (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.